St. Petersburg dialogues, or, Conversations on the temporal government of Providence - Maistre, Joseph Marie, comte de, 1753-1821.; Lebrun, Richard A. (Richard Allen), 1931- (Montréal : McGill-Queens University Press, 1993)
Analisa a providência divina, o bem e o mal, o sacrifício e a teoria cristã sobre o sacrifício humano.
The St Petersburg Dialogues. First Dialogue. Second Dialogue. Third Dialogue. Fourth Dialogue. Fifth Dialogue. Sixth Dialogue. Seventh Dialogue. Eighth Dialogue. Ninth Dialogue. Tenth Dialogue. Eleventh Dialogue. Sketch of a final Dialogue -- Elucidation on Sacrifices. 1. On Sacrifices in General. 2. Of Human Sacrifices. 3. The Christian Theory of Sacrifices.
Translation of: Les soirées de Saint-Pétersbourg.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Providence and government of God; Good and evil; Sacrifice; Bien; Good and evil; Mal; Providence and government of God; Providence divine; Sacrifice; Providence divine; Bien; Mal; Sacrifice; RELIGION -- Christian Theology -- General; PHILOSOPHY -- Religious; Good and evil; Providence and government of God; Sacrifice; Providence; Bien et mal; Sacrifice; Politics -- Philosophy